Effects of intensive and alternative production systems on the technological and quality parameters of rapeseed seed (Brassica napus L. 'Siska'). (21st November 2016) - Turinek, Maja; Bavec, Martina; Repič, Milan; Turinek, Matjaž; Krajnc, Andreja Urbanek; Möllers, Christian; Tres, Alba; Bavec, Franc
Abstract: BACKGROUND: Organic production is widely assumed to affect quality and nutritional parameters of arable crops. A field experiment was started in 2009 following integrated (INT), organic (ORG) and biodynamic (BD) production standards for wheat, maize and rapeseed production. With resort to standard analytical procedures and chemometrics, compositional parameters of Brassica napus L. 'Siska' seed (water, protein, oil and glucosinolate content) by non‐destructive near‐infrared spectroscopy (NIRS), and fatty acid composition determined by gas chromatography, were assessed. RESULTS: The BD and ORG production systems positively influenced oleic fatty acid and oil content in comparison to INT, which had higher levels of protein and water content (19.8% and 4.7%, respectively), as well as linolenic (3.8%), gadoleic (12.6%) and hexadecadienoic (15.5%) fatty acids. Increases in the listed parameters were linked to mineral fertilizer application in the INT production system. With principal component analysis (PCA) the INT samples were clearly differentiated. The PCA results were influenced by differences in linolenic, gadoleic and behenic fatty acid levels as well as protein and water content. CONCLUSION: Because quality parameters in rapeseed are increased in alternative production systems, production with an understanding of the soil processes and yield formation presents an opportunity for ORG and BD farmers. © 2016 Society of Chemical Industry